Impact of Oral Health Knowledge and Attitude on Gingival Health Status - Nadia Rahouma; Raja Barioun (AlQalam Journal of Medical and Applied Sciences, 2023)
Aims. The aim of the present study is to assess the impact of oral health knowledge and attitude on gingival health status among dental students at the University of Tripoli, Libya. Methods. This cross-sectional study was conducted on 160 dental students, all of whom were healthy and of comparable ages. The clinical examination includes the Silness & Loe Plaque Index, 1964 for oral hygiene evaluation and the Loe & Silness Gingival Index (GI), 1967 for the severity of gingival inflammation. Results. The average Plaque index (PI) for the entire students was 0.86 ± 0.42, which reflects the good oral hygiene of students. The mean GI score for participants was 1.01 ± 0.50, which shows moderate gingivitis. Conclusion. This study emphasized the need to enhance dentistry students’ oral health knowledge, attitude, and practice. Inflammation of the gingiva was quite common among dental students.